2006
DOI: 10.1111/j.1475-6773.2006.00629.x
|View full text |Cite
|
Sign up to set email alerts
|

Do Professional Interpreters Improve Clinical Care for Patients with Limited English Proficiency? A Systematic Review of the Literature

Abstract: Objective. To determine if professional medical interpreters have a positive impact on clinical care for limited English proficiency (LEP) patients. Data Sources. A systematic literature search, limited to the English language, in PubMed and PsycINFO for publications between 1966 and September 2005, and a search of the Cochrane Library. Study Design. Any peer-reviewed article which compared at least two language groups, and contained data about professional medical interpreters and addressed communication (err… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
833
4
28

Year Published

2008
2008
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 1,120 publications
(922 citation statements)
references
References 40 publications
16
833
4
28
Order By: Relevance
“…Similar to all prior inpatient studies we found a low use of interpreters by hospital clinicians. 5,6,21 Federal law, the Institute of Medicine (IOM), and hospital guidelines, including the Joint Commission standards, all recommend the routine use of professional interpreters during clinical encounters. 3,[22][23][24] It is possible that our low rate of interpreter use is due to the use of nonprofessional interpreters (i.e., family members or friends) and/or clinical encounters with bilingual physicians or other clinical staff and/or even LEP patients relying on their own limited English language abilities.…”
Section: Mutltivariable Analyses Of Hospital Outcomesmentioning
confidence: 99%
See 2 more Smart Citations
“…Similar to all prior inpatient studies we found a low use of interpreters by hospital clinicians. 5,6,21 Federal law, the Institute of Medicine (IOM), and hospital guidelines, including the Joint Commission standards, all recommend the routine use of professional interpreters during clinical encounters. 3,[22][23][24] It is possible that our low rate of interpreter use is due to the use of nonprofessional interpreters (i.e., family members or friends) and/or clinical encounters with bilingual physicians or other clinical staff and/or even LEP patients relying on their own limited English language abilities.…”
Section: Mutltivariable Analyses Of Hospital Outcomesmentioning
confidence: 99%
“…Several studies show that when LEP patients have access to an interpreter, they actually have increased utilization of services and have improved disease-specific process measures/testing and outcomes. 5 It is possible that the sicker LEP patients required more appropriate medical care or that sicker LEP patients lacked a regular source of medical care, therefore getting most of their workup as an inpatient. In addition, one study has shown that the LOS for LEP patients was longer for seven of 23 medical and surgical conditions.…”
Section: Mutltivariable Analyses Of Hospital Outcomesmentioning
confidence: 99%
See 1 more Smart Citation
“…The language barrier has been associated with poor patient comprehension because the patient may not understand the clinician’s requests, lack the health vocabulary to accurately report symptoms or may recount information in an illogical or fragmented manner [38]. The use of either medically trained or ad hoc translators can reduce the impact of these problems, but do not eliminate them [39]. …”
Section: Study Limitationsmentioning
confidence: 99%
“…Health care professionals face potential civil liability when they fail to provide qualified interpreters, if such failure leads to a tort cause of action, such as lack of informed consent, breach of duty to warn, or improper medical care [15]. In contrast, the use of professional interpreters while providing medical care for patients with LEP improves comprehension, service utilization, clinical outcomes, and patient satisfaction [16].…”
Section: Medical Interpretingmentioning
confidence: 99%